Integration of Islamic Accounting Principles in Islamic Financial Institutions: Accountant’s Perspective and Analysis - Lutfi Rohmah Aini; Malta Anantyasari (JIIS - Journal of Interdisciplinary Islamic Studies, 2026)
This study aims to analyze accountants' perceptions regarding the integration of Sharia accounting principles in Islamic financial institutions in Pacitan, focusing on case studies at BMT Tawakkal and BMT Muamalah. This research employs a qualitative approach through in-depth interviews with accountants directly involved in the implementation of Sharia accounting principles in these institutions. The findings reveal that while most Sharia accounting principles, such as transparency, fairness, and the avoidance of riba (usury), have been implemented, several principles have not been fully applied. The main challenge faced is the pressure to achieve high profit margins, which sometimes conflicts with the ideals of Sharia accounting. Therefore, strategic and innovative solutions are needed to ensure more consistent application of Sharia accounting principles, creating a balance between commercial gains and Sharia values. Ultimately, this is expected to bring blessings and justice in the eyes of Allah for all Sharia-compliant business actors